Cross-Linguistic Intertranslatability of Culturally Loaded Terms - Suparto Suparto (Prasasti: Journal of Linguistics)
The paper tests if the translation of Javanese local cultural terms can denotatively be conveyed in English. The tool employed for this purpose is componential analysis of meaning, which can objectively asses the accuracy of the translation. In addition to this analysis, this study also discusses connotative assigned to the cultural terms by native speakers of Javanese and English. Connotative meanings were determined by collecting data from native speakers via questionnaires. The responses indicate which connotative meanings the respondents assigned to local cultural terms and their English equivalents. The findings indicate that at the denotative level, local cultural terms are very problematic. It is driven by the fact that though translators have tried to find the closest equivalents in the target language, there are still semantic features that differentiate both the source text and the target text. It demonstrates that full intertranslatability of cultural terms is not possible at denotative level. This study classifies the results of the translation into five classifications: (1) both the denotation and the connotation are different; (2) different denotations but the same connotations; (3) both of denotations and connotations are identical or near identical; (4) generic target text; and (5) specific target text. The findings show that respondents can attribute connotations to cultural terms only if they have been exposed to them and are familiar with the concepts that they convey. The connotations can semantically be classified into good or bad; active or passive; and strong or weak. It is also shown that people of the same cultural background do not always have the same connotations. Their prior knowledge plays and important role in determining what kind of connotations they yield. It is clear that connotations consist of posteriori knowledge.